THE EFFECT OF ULTRAVIOLET RAYS ON THE RESISTANCE OF MICROFLORA IN THE TREATMENT OF PURULENT-SURGICAL DISEASES OF SOFT TISSUES - Latipov Orif Zaripovich (Scholar Express Journals, 2022)
Wound infection, including postoperative infection, continues to be one of the most pressing problems in surgery. Solving the problems associated with microflora resistance undoubtedly improves the results of treatment for this category of patients. In the literature, there are significantly few studies devoted to the suppression of the existing microflora resistance. The purpose of the study: study of the influence of ultraviolet rays on the resistance of the microflora of purulent wounds. In 22 patients with purulent diseases of soft tissues, resistance to 15 antibiotics was studied on the day of admission and in the dynamics of local treatment using ultraviolet irradiation (UFO) of the wound in two biodoses. The results of the study showed: the treatment of purulent wounds with the use of ultraviolet irradiation of the wound in two biodoses, in addition to the bactericidal one, has an overwhelming effect on the resistance of microflora
Keywords: purulent wound; resistance; ultraviolet irradiation